2016
DOI: 10.3109/21691401.2016.1138487
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNAs expression in hematopoietic stem cells treated with sodium butyrate in inducing fetal hemoglobin expression

Abstract: Context Inherited hemoglobin diseases are the most common single-gene disorders. Induction of fetal hemoglobin in beta hemoglobin disorders compensate for abnormal chain and ameliorate the clinical complications. Sodium butyrate is used conventionally for fetal hemoglobin induction; it can be replaced by safer therapeutic tools like microRNAs, small non-coding RNAs that control number of epigenetic mechanisms. Objective In this study, we compared the changes in the microRNAs of differentiated erythroid cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Several research efforts have focused on identifying miRNA genes that regulate HBG expression during haemoglobin switching (Gasparello et al , ; Hojjati et al , ; Lai et al , ; Sun et al , ; Obeidi et al , ; Saki et al , ; Tayebi et al , ; Guda et al , ; De Vasconcellos et al , ; Bianchi et al , ). Bianchi et al () identified the upregulation of MIR210 by microarray analysis of erythroid precursors from a thalassaemia patient with high HbF levels; they also demonstrated that mithramycin targeted MIR210 as a mechanism of HBG activation in K562 cells (Bianchi et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several research efforts have focused on identifying miRNA genes that regulate HBG expression during haemoglobin switching (Gasparello et al , ; Hojjati et al , ; Lai et al , ; Sun et al , ; Obeidi et al , ; Saki et al , ; Tayebi et al , ; Guda et al , ; De Vasconcellos et al , ; Bianchi et al , ). Bianchi et al () identified the upregulation of MIR210 by microarray analysis of erythroid precursors from a thalassaemia patient with high HbF levels; they also demonstrated that mithramycin targeted MIR210 as a mechanism of HBG activation in K562 cells (Bianchi et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the roles of butyrate in regulating expression of encoded genes have been intensively investigated; however, there are few reports on noncoding RNAs, especially on microRNAs. In NaB treated hematopoietic stem cells, 76 microRNAs were significantly induced such as hsa‐miR‐4726‐5p, hsa‐miR7109‐5p, hsa‐miR3663, and hsa‐miR940 screened by microarray . In HCT‐116 cells, microarray was also used to detect the microRNAs response to butyrate treatment, 44 miRNAs were found to be significantly changed in expression .…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that sodium butyrate treatment can be replaced by safer therapeutic tools like microRNAs, small non-coding RNAs that control number of epigenetic mechanisms. In a study by Tayabi and colleagues, it was demonstrated that gamma chain was 5.9-fold up-regulated in the treated group [84].…”
Section: Archives Of Medicine Issn 1989-5216mentioning
confidence: 97%
“…Instead of leaving the cell to make its own error-prone repairs to the CRISPR-induced cuts, researchers supply further guidance by delivering a strand of DNA that contains the corrected snippet of the haemoglobin sequence-a kind of 'repeat after me'. This approach is called homologydirected repair [84].…”
mentioning
confidence: 99%